Marijuana Use as a Sex-Drug is Associated with HIV Risk Among Black MSM and Their Network - Morgan, Ethan (AIDS Behav, 2016)
INTRODUCTION: Black men who have sex with men (BMSM) are highest risk for HIV seroconversion in the United States. Little attention has been paid to marijuana use among BMSM and potential for HIV risk. METHODS: A sample of 202 BMSM was generated through respondent driven sampling. The relationship between differential marijuana use and both HIV risk behavior and social network factors were examined using weighted logistic regression. RESULTS: Of the BMSM in this sample 60.4% use marijuana in general and 20.8% use marijuana as sex-drug. General marijuana use was significantly associated with participation in group sex (AOR 3.50; 95% CI 1.10–11.10) while marijuana use as a sex drug was significantly associated with both participation in condomless sex (AOR 2.86; 95% CI 1.07–7.67) and group sex (AOR 3.39; 95% CI 1.03–11.22). Respondents with a moderate or high perception of network members who use marijuana were more likely to use marijuana both in general and as a sex-drug. CONCLUSION: Network member marijuana use, while not associated with risk behaviors, is associated with individual marijuana use and individual marijuana use in the context of sex is associated with risk practices. Targeting interventions towards individuals and their respective networks that use marijuana as a sex drug may reduce HIV risk.